Self Management, Self Esteem, And Body Image on Job Opportunities in Malang City - Muhammad Adel; Almanshur, Fauzan (Jurnal Ilmu Manajemen Advantage, 2024)
Human resources are the fundamental capital in the national development process. Currently, the competition for job opportunities is becoming increasingly fierce, and the number of available jobs is dwindling. This has led to a high level of unemployment. Malang City is ranked fifth in the Open Unemployment Rate (Tingkat Pengangguran Terbuka, TPT) in East Java, following Sidoarjo Regency, Batu City, Bangkalan Regency, and Gresik Regency. This research aims to examine the influence of self-management, self-esteem, and body image on job availability in Malang City. The research method employed is quantitative through a survey using primary data. Information was collected by distributing questionnaires to a sample of 100 fresh graduate students. The sampling method used was accidental sampling. Data analysis techniques included multiple linear regression, t-test, and F-test. The research results indicate that self-management, self-esteem, and body image, when considered together, collectively have a positive and significant impact on job availability for job seekers. However, individually, body image does not significantly affect job availability.